A review on methane transformation to hydrogen and nanocarbon: Relevance of catalyst characteristics and experimental parameters on yield - Ashik, U.P.M.; Daud, Wan Mohd Ashri Wan; Hayashi, J.I. (Elsevier, 2017)
Co-synthesis of hydrogen and nanocarbon via methane cracking is a single step technique which meets ever growing need of greenhouse gas (GHG) free energy. Additionally, as produced multifunctional nano-carbon that have a variety of technological applications reduces the process cost. This review is intended to provide a critical and wide-ranging assessment of impact of metal catalyst characteristics and methane decomposing parameters on hydrogen and nanocarbon yield, as well as the alteration of characteristic properties of as-produced nanocarbon. The major factors influencing thermocatalytic decomposition of methane (TCD) includes catalyst support, porosity, surface area, particle size, metal loading, calcination temperature, feed flow rate, partial pressure, and reaction temperature. Literature survey emphasizes that higher temperature and partial pressure together with lower feed flow is the reliable experimental condition to yield high purity hydrogen. Furthermore, initial catalytic activity resembles to the chemical structure of the catalyst and long term activity corresponds to the physical characteristics of catalyst. The structural features of as-produced nanocarbon have inevitable association with catalytic characteristics, such as textural supporters, particle size and material dispersion by physical interactions or chemical interaction. The interaction of metal and support results in modification of electronic properties of metal particles and subsequently influence their catalytic characteristics. In addition to investigation of one-factor-at-a-time experiments, the latest studies with Design of Experiment are also thoroughly reviewed, which analyze the influence of each process variables and their interactions simultaneously. The manuscript, then, extended to the microscopic level understandings on TCD for synthesis of nanocarbon and hydrogen via computational study in the finishing section.